The Implementation of Using Numbered Head Together (NHT) Learning Model to Improve Students’ Speaking Achievement - Kusuma, Dewinta Dwi; Rahayu, Endang Mastuti (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
The purpose of the study was to describe the implementation of the Numbered Head Together (NHT) Learning model to improve students' speaking achievement. The students' pretest results led to this study's conduct. Merely ten pupils surpassed the minimal scoring requirements (KKM). The Classroom Action Research (CAR) research method was employed. This research was conducted at SMAN 4 Sidoajo. The subject of this research was the first-grade students (10th) in SMAN 4 Sidoarjo. The participants were from class X-K, consisting of 40 students (17 males and 23 females). This research was carried out from November 16 until December 7, 2023. The tools were a questionnaire, an observation sheet, and a subjective test. Observations were analyzed using descriptive qualitative. Subjective tests were analyzed using the percentage of data. Questionnaires were analyzed using quantitative Percentage data. The students' speaking scores improved from 78% to 90%; out of 40 students, 36 passed the test. Additionally, there was an increase in the student's participation on the observation sheet and in their answers to the Questionnaire Questionnaire distributed at the previous meeting. As a result, teaching with the NHT learning approach can improve students' speaking achievement.